2016
DOI: 10.3341/kjo.2016.30.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Patients with Branch Retinal Vein Occlusion: A Preliminary Study

Abstract: PurposeOur study aimed to determine whether obstructive sleep apnea (OSA) is common among branch retinal vein occlusion (BRVO) patients without systemic risk factors using a Watch PAT-100 portable monitoring device.MethodsThe study participants included consecutive patients with BRVO of less than 3 months duration without any risk factors known to be associated with OSA (diabetes, coronary artery disease, stroke, hematologic diseases, autoimmune disease, etc.) except for hypertension. All patients underwent fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Three recent meta-analyses of RVO and thrombophilic factors demonstrated that only hyperhomocysteinemia and anticardiolipin antibodies play a role in the pathogenesis of RVO [24, 29, 51]. Additional studies also reported other less common risk factors such as obstructive sleep apnea (OSA), inadvertent retrobulbar needle perforation, axial length and vitreous chamber depth, liver or renal diseases, and even posterior vitreous adhesion [5257]. Moreover, BRVO may also be easier to find in people with gene defects, like adiponectin +276 G/T and AGTR1 A1166C single-nucleotide polymorphism, which are related to arterial stiffness [58].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Three recent meta-analyses of RVO and thrombophilic factors demonstrated that only hyperhomocysteinemia and anticardiolipin antibodies play a role in the pathogenesis of RVO [24, 29, 51]. Additional studies also reported other less common risk factors such as obstructive sleep apnea (OSA), inadvertent retrobulbar needle perforation, axial length and vitreous chamber depth, liver or renal diseases, and even posterior vitreous adhesion [5257]. Moreover, BRVO may also be easier to find in people with gene defects, like adiponectin +276 G/T and AGTR1 A1166C single-nucleotide polymorphism, which are related to arterial stiffness [58].…”
Section: Risk Factorsmentioning
confidence: 99%
“…78 Other retinal changes described in OSA included retinal arteriolar narrowing and venular widening or branch retinal vein occlusion. 79,80…”
Section: Osa and Microvascular Complications In T2dmentioning
confidence: 99%
“…78 Other retinal changes described in OSA included retinal arteriolar narrowing and venular widening or branch retinal vein occlusion. 79,80 In patients with T2D, the relationship between OSA and DR is complex and the results of multiple studies were inconsistent; this is, in part, due to the poor methodology of some of the available literature. A recent systematic review found that out of 16 studies that examined the relationship between OSA and DR, 15 were cross-sectional in nature and 1 cohort study, 81 which highlights the need for more robust studies in this area.…”
Section: Osa and Retinopathymentioning
confidence: 99%
“…Выявленная разница в толщине хориоидеи оказалась несущественной. В обеих группах отмечена обратная зависимость между длиной передне-задней оси глазного яблока и коэффициентом Янтча (r=-0,51, r=-0,45), амплитудой глазного пульса (r=-0,52 r=-0,28) и пульсовым объемом переднего сегмента (r=-0,46 r=-0,32 [29].…”
Section: результаты исследованияunclassified